Ovariohysterectomy in Cat as An Alternative Handling of Fetus Mummification Cases - Ercha Aulia Putri, Cindy; Safitri, Erma; Syafitri, Winda (Universitas Airlangga, 2025)
Fetal mummification is a rare and challenging condition in cats that requires immediate intervention to mitigate potential risks to the mother and future pregnancies. This case study presents the diagnosis, treatment, and outcomes of Pawpaw, a cat diagnosed with fetal mummification. Ovariohysterectomy was performed as an alternative treatment method to address the critical condition of the cat. The diagnosis was established based on various factors, including indications, anamnesis, clinical symptoms, clinical examination, clinical findings, and investigative results. Diagnostic confirmation was achieved through blood haematology tests and ultrasound examinations. The therapeutic approach consisted of administering a combination of normal saline fluid therapy, glycerin, ondansetron, ceftriaxone, intramox, doxycycline, acetylcysteine, sakatonic liver, vitamins, ventolin, Tripura, meloxicam, impacting, and furosemide. Anesthesia during the ovariohysterectomy procedure involved the use of atropine sulfate, xylazine, and ketamine. Despite the extensive medical intervention, the cat, Bimbim, succumbed to its critical condition during the surgery. This case study highlights the importance of early diagnosis and prompt intervention in cases of feline fetal mummification. Ovariohysterectomy proved to be a viable alternative treatment option, although the critical condition of the cat posed significant challenges to its successful outcome. Further research and enhanced understanding of fetal mummification in cats are essential to improve the management and prognosis of this condition.